PERANCANGAN MODEL MEDIA PEMBELAJARAN BAHASA INDONESIA BERBASIS TIK - Annisa Anabella (BADAN PENERBIT STIEPARI PRESS, 2022)
Education is needed as a business that has the main goal of forming human beings with potential and quality in all aspects of life. The formation of quality human resources in a developing country to a developed country is greatly influenced by the existence of education. This study aims to discuss in detail the design of ICT-based Indonesian language learning media to support learning activities. The use of ICT-based learning media has not been widely developed, especially for Indonesian language subjects. The implementation of ICT-based learning media needs to be applied so that in the learning process a new atmosphere occurs so that students can overcome the times. This study uses content analysis techniques with a qualitative approach by analyzing the concept of Indonesian language learning based on ICT.